Velopharyngeal Closure and Resonance in Children Following Early Cleft Palate Repair: Outcome Measurement - Aparna, V. S.; Pushpavathi, M.; Bonanthaya, Krishnamurty (Indian Journal of Plastic Surgery, 2019)
Introduction Timing of cleft palate repair and the method of speech outcome measurement in children with cleft lip and palate are much debated topics. The associated problems and quality of life in these children depend on the timing of the surgery.Aim The aim of this study was to investigate the velopharyngeal (VP) function and resonance parameters in children following early cleft palate repair.Method A total of 25 Kannada-speaking children with early repaired cleft palate were subjected to speech assessment and videofluoroscopic assessment. Perceptual speech parameters measured were severity of hypernasality and presence of nasal air emission. Videofluoroscopy was interpreted in terms of closure ratios to predict the severity of VP dysfunction.Results The analysis of videofluoroscopic images indicated that 48% of children had complete VP closure and 52% had perceptually normal resonance. A good correlation was found between the closure ratio and hypernasality.Conclusion Understanding the perceptual speech parameters and their structural correlates for outcome measurement will give better evidence for refining the existing treatment protocols. Data on a larger population are warranted for establishing predictors of optimum speech outcome.
Keywords: videofluoroscopy; perceptual speech; hypernasality; nasal air emission; closure ratio